2023
DOI: 10.1007/s12649-023-02127-2
|View full text |Cite
|
Sign up to set email alerts
|

Direct Conversion of N-acetyl-d-glucosamine to N-containing Heterocyclic Compounds 3-Acetamidofuran and 3-Acetamido-5-acetyl Furan

Abstract: Effectual waste utilization from plant as well as marine biomass has gained tremendous importance with reference to sustainability. The valorization of marine biomass produces value added compounds containing not only C, H, O but also renewable N atom in the skeleton which widens the scope for its exploration which may prove to be economically bene cial to the society. Heterogeneous catalytic transformation of marine biomass i.e. N-acetyl glucosamine (NAG) to N-substituted aromatic heterocyclic is reported for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…3AF and 3A5AF were identified as the major products with 50% and 21% yields in dioxane under optimal conditions. 103 La 2 O 3 displayed a nano-pore structure and acted as a weak Brønsted base, which conducted the dehydration pathway to the 3AF. It was regenerated after successive filtration, wash, dry and calcination.…”
Section: Dehydrationmentioning
confidence: 99%
“…3AF and 3A5AF were identified as the major products with 50% and 21% yields in dioxane under optimal conditions. 103 La 2 O 3 displayed a nano-pore structure and acted as a weak Brønsted base, which conducted the dehydration pathway to the 3AF. It was regenerated after successive filtration, wash, dry and calcination.…”
Section: Dehydrationmentioning
confidence: 99%
“…Shaikh et al reported that lanthanum oxide catalyzed the conversion of NAG to 3A5AF as a heterogeneous catalyst. [9] 3A5AF formation from NAG proceeds via ring opening of NAG, formation of a five-membered ring, and dehydration. [7] Chloride ion catalyzes the ring opening of NAG and formation of the five-membered ring, [7] as well as the subsequent dehydration.…”
Section: Introductionmentioning
confidence: 99%
“…Shaikh et al. reported that lanthanum oxide catalyzed the conversion of NAG to 3A5AF as a heterogeneous catalyst [9] . 3A5AF formation from NAG proceeds via ring opening of NAG, formation of a five‐membered ring, and dehydration [7] .…”
Section: Introductionmentioning
confidence: 99%